Alternative Scheme for Handling Reversely the Waste of Mobile Phone in Bandung, Indonesia - Bagus Arthaya; Eliza Nathania (Universitas Lampung, 2017)
Abstract—Waste and other second-hand goods management in Indonesia are still not properly managed, while used products still have their economic value. E-waste is one of many second-hand goods that are not handled properly. E-waste is defined as the rubbish of electronic products. Mobile phone is one of the electronic products that are almost used by most of Indonesian people, ranging from people having low income to those having a huge income. The influence of lifestyle makes mobile phone lifespan is very short. High level of consumption and short life time make mobile phones are not used accordingly and quickly become waste. When this waste is not managed properly then it will accumulate and damage our nature, because almost all mobile phone components are non-organic materials. Used mobile phones still have economic value and some of their components can be recycled or reused. Therefore this study focuses on promoting reverse handling management of used mobile phones from the Indonesian consumers. The main strategy is aligned with Reverse Logistics concept where value recovery and proper disposal become the main consideration. In this design, a strategy will be discussed throughout the stakeholders who will be involved in the return process so the process can run effectively and efficiently. Consideration of recycling or reusing used product can reduce the retrieval of raw materials from the nature. The problem solution will certainly have an impact on our natural resources balance. When this strategy works successfully then it will certainly contribute in preserving of nature.Keywords— economic value, e-waste, recycle and reuse, reverse logistic, used product.